2020
DOI: 10.3389/fphar.2020.585876
|View full text |Cite
|
Sign up to set email alerts
|

Functionalized Oxoindolin Hydrazine Carbothioamide Derivatives as Highly Potent Inhibitors of Nucleoside Triphosphate Diphosphohydrolases

Abstract: Ectonucleoside triphosphate diphosphohydrolases (NTPDases) are ectoenzymes that play an important role in the hydrolysis of nucleoside triphosphate and diphosphate to nucleoside monophosphate. NTPDase1, -2, -3 and -8 are the membrane bound members of this enzyme family that are responsible for regulating the levels of nucleotides in extracellular environment. However, the pathophysiological functions of these enzymes are not fully understood due to lack of potent and selective NTPDase inhibitors. Herein, a ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 40 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…In the 3-position, a cyano group (10,19,20), an ethylcarboxylic acid ester (1-4, 11-15, 17), or a tert-butylcarboxylic acid ester (5-9, 16, 18, 21-32) was present. Position 2 was substituted with an amino group (1-10), a benzamido residue (11), a thiourea group (12)(13)(14)(15)(16)(17)(18)(19), a cyclized isothiourea group (20), a urea (21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32), or a carbamate (27) function. R 1 position: A small aliphatic methyl or ethyl substituent resulted in inactive compounds (1, 2, 5, and 6), while a larger, more lipophilic isobutyl residue restored some potency (compound 7); however, a benzyl residue was superior (4,8,10).…”
Section: Structure-activity Relationships (Sars)mentioning
confidence: 99%
See 2 more Smart Citations
“…In the 3-position, a cyano group (10,19,20), an ethylcarboxylic acid ester (1-4, 11-15, 17), or a tert-butylcarboxylic acid ester (5-9, 16, 18, 21-32) was present. Position 2 was substituted with an amino group (1-10), a benzamido residue (11), a thiourea group (12)(13)(14)(15)(16)(17)(18)(19), a cyclized isothiourea group (20), a urea (21)(22)(23)(24)(25)(26)(28)(29)(30)(31)(32), or a carbamate (27) function. R 1 position: A small aliphatic methyl or ethyl substituent resulted in inactive compounds (1, 2, 5, and 6), while a larger, more lipophilic isobutyl residue restored some potency (compound 7); however, a benzyl residue was superior (4,8,10).…”
Section: Structure-activity Relationships (Sars)mentioning
confidence: 99%
“…Only a few small molecule inhibitors of CD39 have been described so far, all of which show limited potency and/or lack of metabolic stability. [26][27][28][29][30][31][32] Nucleotide derivatives, analogs of the natural substrates, have been investigated, for example, ARL 67156 (I) and its derivatives (e.g., II). [27,33,34] Nonnucleotide inhibitors comprise polyoxometalates (POMs, e.g., III), anthraquinones, and various other heterocyclic compounds including the clinically approved drugs ticlopidine (IV) and clopidogrel (V), and indole derivatives such as VI.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expanding research on the hydrazine-based molecule is evident from the world hydrazine market value which is US$424 million in 2020 as per the report by Future Market Insight (FMI) and in 2021 the value surpassed US$426 million [8]. On the verge of the development of efficient hydrazine-based materials, many functionalizations have been achieved [9][10][11][12]. The functionalization of hydrazine improves the efficiency of the materials and may create new properties in it.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the development of ecto-5′-nucleotidase inhibitors may also serve to treat cancer (Iqbal et al, 2013). The heterocyclic compounds which have been synthesized and screened as NTPDases include oxoindolin phenylhydrazine carboxamides (Afzal et al, 2021), pyrrolo[2,3-b]pyridine derivatives (Ullah et al, 2021), spirooxindole derivatives (Ashraf et al, 2020), sulfonylhydrazones (Younus et al, 2020), 2-substituted-7trifluoromethyl-thiadiazolopyrimidones (Afzal et al, 2020), pyrazolyl pyrimidinetrione, and thioxopyrimidinedione conjugates as selective inhibitors of human ectonucleotidase (Andleeb et al, 2019), etc. Furthermore, the review articles of Iqbal (Iqbal, 2019) have also reported the importance of ectonucleotidase inhibitors in the treatment of various diseases.…”
mentioning
confidence: 99%